1998
DOI: 10.1021/jp972743l
|View full text |Cite
|
Sign up to set email alerts
|

Energetics and Mechanism of Primary Charge Separation in Bacterial Photosynthesis. A Comparative Study on Reaction Centers of Rhodobacter sphaeroides and Chloroflexus aurantiacus

Abstract: The high efficiency of charge separation in photosynthetic reaction centers arises from the interplay of energetics, electronic couplings, and reorganization energies relevant for the fast charge separation and slow recombination processes. All these parameters can be determined unambiguously only from magnetic-fielddependent measurements of the recombination dynamics of the intermediate radical pair P + H A -and the lifetime of the recombination product 3 P*. Results obtained on Q A -depleted reaction centers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
98
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(113 citation statements)
references
References 114 publications
(365 reference statements)
15
98
0
Order By: Relevance
“…There P + H L -decays with a lifetime of ∼10 ns at 295 K and ∼20 ns at 77 K, although the precise lifetime as well as the fraction of charge recombination that leads to the ground state versus 3 P depends on conditions. 26,71,[113][114][115][116] Overall our results here indicate that the temperature dependence of P + H M -decay is similar to that of P + H L -in showing a small decrease between 295 and 77 K.…”
Section: Heterogeneous-rc Model For D Llsupporting
confidence: 75%
See 1 more Smart Citation
“…There P + H L -decays with a lifetime of ∼10 ns at 295 K and ∼20 ns at 77 K, although the precise lifetime as well as the fraction of charge recombination that leads to the ground state versus 3 P depends on conditions. 26,71,[113][114][115][116] Overall our results here indicate that the temperature dependence of P + H M -decay is similar to that of P + H L -in showing a small decrease between 295 and 77 K.…”
Section: Heterogeneous-rc Model For D Llsupporting
confidence: 75%
“…[55][56][57] Additionally, calculations generally place the P + B -state higher in free energy than the P + H -state on both L and M branches by 0.15-0.25 eV, consistent with the difference in redox potentials of bacteriochlorophyll and bacteriopheophytin in vitro. [58][59][60][61] Calculations and experiments have provided estimates or bracketed ranges for the free energies of the charge-separated states in the wild-type RC: P + B L -0.05-0.1 eV below P*; 29,50,51,[62][63][64][65][66][67][68][69][70] P + H L -∼0.25 eV below P* when relaxed; [71][72][73][74][75] P + B M -0.1-0.2 eV above P* and P + H M -below P* by no more than ∼0.15 eV and probably within 0.1 eV. [50][51][52][76][77][78][79] Systematic efforts to manipulate the free energy differences of the L-and M-branch charge-separated states by site-directed mutagenesis of key amino acids, including those near B M and B L , have led to mutant RCs in which electron transfer to the M branch competes effectively with charge separation to the L branch, yielding P + H M -(reviewed in ref 80).…”
Section: Introductionmentioning
confidence: 99%
“…5,6 The resulting bestfit reorganization energies for primary charge separation have evolved over the years from very low magnitudes ≈0.06-0.1 eV in earlier studies [7][8][9] to 0.19 eV later on, 10 and to a noticeably larger magnitude of 0.35 eV in more recent fits. 11 The situation with the available database of electron-transfer reorganization parameters has improved in the recent decade with the widespread of numerical simulations of biological systems.…”
Section: Introductionmentioning
confidence: 90%
“…State 3 can recombine to the original ground state P on the nanosecond time scale. 10 An additional recombination channel of state 3 is to a photoexcited triplet of the special pair, 3 P* (state 4). The energy gaps between P and P* and between P and 3 P* are known from experimental spectroscopic measurements, 10 while the free energy gaps between other states shown in Figure 2 are from our calculations described below.…”
Section: Modelmentioning
confidence: 99%
“…Recent measurements by Volk et al 46 and the calculation of Sim and Makri 47 suggested that ∆G WT for the first step of ET in the wild type Rb. sphaeroides is -0.05 eV.…”
Section: Methodsmentioning
confidence: 99%